Reward–Penalty Mechanism Based on Daily Energy Consumption for Net-Zero Energy Buildings - Yang Zhang (MDPI AG, 2021)
Net-zero energy buildings (ZEB/NZEB) have been greatly encouraged and are considered to be a promising approach for energy conservation as well as environmental protection. However, a lack of incentive mechanisms can hinder the fast development and application of ZEB. This study thus focuses on the design of a daily reward–penalty mechanism (RPM) by considering the performance of the building, aiming to enable a lower penalty cost for the building where there is a better match between energy consumption and energy generation. The impact of the degree of freedom of the building load (k) is investigated on building performance based on a single-family house located in Shanghai city, China. It is observed that a higher value of k is preferred since the building users can adjust its energy consumption profile to better match with its energy generation. A higher k value enables lower annual energy consumption, lower penalty cost, better stability, and an average daily zero energy level of around 1.0. In addition, four quadratic fit curves are derived to describe the relationship between building performance (i.e., annual energy consumption, the average daily zero energy level, stability, and annual penalty cost) and the degree of freedom. Meanwhile, the uncertainty of ZEB performance is quantified, which provides flexibility for building users in selecting the appropriate degree of freedom.